1996
DOI: 10.1002/food.19960400109
|View full text |Cite
|
Sign up to set email alerts
|

Comparing effects of washing, thermal treatments and gamma irradiation on quality of spieces

Abstract: Selected five spices were treated with simple natural methods as washing with pure tap water then drying at room temperature, thermal treatment at 70 -C/IS minutes hesides irradiation with 5.0 and 1 0 kCiy. The cvalualion of the used treatments efficiency depends on microbiological and chemical studies. The results show that untreated samples were highly contaminated with pathogenic and toxigenic microbes. Gamma irradiation was effective i n decontamination especially 10 kGy but caused losses in major componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 11 publications
2
2
1
Order By: Relevance
“…A little increase was also, resulted by thermal treatments. Same results was obtained by (Zaied et al, 1996 ). Table 3.…”
Section: Effect Of Thermal and Irradiation Treatments On Total Phenolsupporting
confidence: 82%
See 1 more Smart Citation
“…A little increase was also, resulted by thermal treatments. Same results was obtained by (Zaied et al, 1996 ). Table 3.…”
Section: Effect Of Thermal and Irradiation Treatments On Total Phenolsupporting
confidence: 82%
“…Whereas the thermal treatments either at long or short time at 50 0 C was less effective in efficiency than irradiation for decontamination of turmeric. These results are in parallel with those obtained by some workers(Zaied et al,1996;Lee, 2004) who reported that irradiation dose of 3.0 kGy without heat treatment reduced the microbial load in coriander, cumin, turmeric and chili from 6 log to 3 log and from 5 log to 2 log units depending on the storage temperature.Table 1. Effect of thermal and irradiation treatments on microbial load of tested turmericTreatments Total bacterial count (CFU/g) Total Fungi count (CFU/g) Effect of heat and irradiation treatments on antimicrobial activity of turmeric In the present work ethyl extract was chosen rather than other solvents due to its potential as showed by many workers (Pundir and Jain 2010).…”
supporting
confidence: 90%
“…Moreover, they reported total sesquiterpenes content decreased by increasing irradiation dose which it was more dramatic in modified packaging (N₂) compared with air packaging. Increases in oxygenated hydrocarbon and decreases in monoterpenes of volatile oil of gamma irradiated black pepper was previously reported by Emam et al (1995) andZaied et al (1996). However, our results disagree with dose obtained by Chatterjee et al (2000).…”
Section: Determination Of Minimum Inhibitory Concentration (Mic) Ancontrasting
confidence: 78%
“…It has been confirmed that irradiation may induce oxidation, isomerization, and hydroxylation reactions in plant volatile oil and cause qualitative or qualitative changes of volatile oil's constituents (Emam, Farag, & Aziz, ; Zaied, Aziz, & Ali, ). Kirkin et al () reported that by increasing irradiation doses (7, 12, and 17 kGy) significant increase of oxygenated hydrocarbon observed in of rosemary and black pepper volatile oils which is in accordance with our results.…”
Section: Resultsmentioning
confidence: 99%
“…Another study has reported that the reduction of monoterpenes, such as sabinene and phellandrene, in black pepper after high pressurization at 60 _ 140℃ for 30 min was temperature-dependent (Skapska et al, 2003). Thermal treatment (70℃, 15 min) has been shown to increase the relative ratios of some monoterpenes, including pinene and myrcene (Zaied et al, 1996). Air oven processing (≥ 130℃) resulted in changes in the relative composition of limonene, pinene, and sabinene (Chacko et al, 1996).…”
Section: Discussionmentioning
confidence: 99%